Key Factors Affecting to Construction Insurance on Fire Safety on High Rise Building in Indonesia - Simanjuntak, Manlian Ronald Adventus (Pelita Harapan University, 2001)
The fire damage occurs in unpredictable time and can cause losses to the owner because of the damage. Relevant research indicated Fire Safety Design is very important to detect and prevent against fire damage. The four key variables influencing building reliability in preventing fire damage carried out by the consultant and controlled by the construction manager in the projects and their contribution to the model are: detection and fire alarm (active protection) = 43.3 %, building architecture (passive protection) = 21.2 %, the designers fire certificate = 8.4 % and special equipment to stop fire = 5.3 %. In order to allocate the risk, the construction practice use the insurance contract by paying some of cost (premi) according to the risk of fire damage. There are key factors that influence to the law of construction insurance on fire safety on high rise buildings in Indonesia that will be discussed in this paper. The variables than can measure the premi index in construction insurance to guarantee the assets of buildings and lifes from fire damage.Â